A CMOS image sensor for high-speed active range finding using column-parallel time-domain ADC and position encoder. - Oike, Y.
In this paper, a smart image sensor for real-time and high-resolution three-dimensional (3-D) measurement to be used for sheet light projection is presented. It realizes not only a sufficiently high frame rate for real-time 3-D measurement, but also high pixel resolution due to a small pixel circuit and high subpixel accuracy due to gravity center calculation using an intensity profile. Simulation results show that the ultimate frame rate is 32.6 k frames/s (i.e., 31.8 range_map/s) in a 1024×1024 pixel sensor. A 3-b intensity profile allows subpixel accuracy under 0.1 pixel. The sensor using this architecture can acquire a two-dimensional (2-D) image as well, so a texture-mapped 3-D image can be reproduced by the same sensor. A 128×128 smart image sensor has been developed and successfully tested. A 2-D image, a range map, and a texture-mapped 3-D image have been acquired by the 3-D measurement system using the fabricated sensor.
Keywords: 1024 pixel; 1048576 pixel; CMOS image sensor; Column-parallel time-domain ADC; Frame rate; Gravity center calculation; High-speed active range finding; Intensity profile; Pixel resolution; Position encoder; Sheet light projection; Smart image sensor; Subpixel accuracy